2020
DOI: 10.1088/1742-5468/ab900d
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional Janus fluids. Exact solution and mapping from the quenched to the annealed system

Abstract: The equilibrium properties of a Janus fluid confined to a one-dimensional channel are exactly derived. The fluid is made of particles with two faces (active and passive), so that the pair interaction is that of hard spheres, except if the two active faces are in front of each other, in which case the interaction has a square-well attractive tail. Our exact solution refers to quenched systems (i.e., each particle has a fixed face orientation), but we argue by means of statistical–mechanical tools that the resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The quenched quantities in the TL are provided by equations (2.25), (2.28a), and (2.28b). As proved in Appendix B, equation (2.25) is equivalent to (but more compact than) the Gibbs free energy derived in reference [35] from a completely different method. While in reference [35] the thermodynamic results were derived firectly in the TL from the structural correlation functions, here they have been derived by carefully taking the limit N → ∞ from the configuration integral.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quenched quantities in the TL are provided by equations (2.25), (2.28a), and (2.28b). As proved in Appendix B, equation (2.25) is equivalent to (but more compact than) the Gibbs free energy derived in reference [35] from a completely different method. While in reference [35] the thermodynamic results were derived firectly in the TL from the structural correlation functions, here they have been derived by carefully taking the limit N → ∞ from the configuration integral.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure can be extended in a straightforward way to a biased choice q = 1 2 , which gives rise to x = 1 2 . The naive expectation would be x = q, but preliminary results in reference [35] showed that either 1 2 < x < q or 1 2 > x > q, depending on whether q > 1 2 or q < 1 2 , respectively. One might reasonable wonder whether the property x = q is a finitesize effect that would disappear in the TL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations